Analysis of cell‐free DNA in maternal blood in screening for fetal aneuploidies: updated meta‐analysis. (1st February 2015) - Gil, M. M.; Quezada, M. S.; Revello, R.; Akolekar, R.; Nicolaides, K. H.
Abstract : This article has been selected for Journal Club. Clickhere to view slides and discussion points. Update in "Analysis of cell‐free DNA in maternal blood in screening for aneuploidies: updated meta‐analysis ". ABSTRACT: Objective: To review clinical validation or implementation studies of maternal blood cell‐free (cf) DNA analysis and define the performance of screening for fetal trisomies 21, 18 and 13 and sex chromosome aneuploidies. Methods: Searches of PubMed, EMBASE and The Cochrane Library were performed to identify all peer‐reviewed articles on cfDNA testing in screening for aneuploidies between January 2011, when the first such study was published, and 4 January 2015. Results: In total, 37 relevant studies were identified and these were used for the meta‐analysis on the performance of cfDNA testing in screening for aneuploidies. These studies reported cfDNA results in relation to fetal karyotype from invasive testing or clinical outcome. Weighted pooled detection rates (DR) and false‐positive rates (FPR) in singleton pregnancies were 99.2% (95% CI, 98.5–99.6%) and 0.09% (95% CI, 0.05–0.14%), respectively, for trisomy 21, 96.3% (95% CI, 94.3–97.9%) and 0.13% (95% CI, 0.07–0.20) for trisomy 18, 91.0% (95% CI, 85.0–95.6%) and 0.13% (95% CI, 0.05–0.26%) for trisomy 13, 90.3% (95% CI, 85.7–94.2%) and 0.23% (95% CI, 0.14–0.34%) for monosomy X and 93.0% (95% CI, 85.8–97.8%) and 0.14% (95% CI, 0.06–0.24%) for sex chromosome aneuploidies other than monosomy X. For twin pregnancies, the DR for trisomy 21 was 93.7% (95% CI, 83.6–99.2%) and the FPR was 0.23% (95% CI, 0.00–0.92%). Conclusion: Screening for trisomy 21 by analysis of cfDNA in maternal blood is superior to that of all other traditional methods of screening, with higher DR and lower FPR. The performance of screening for trisomies 18 and 13 and sex chromosome aneuploidies is considerably worse than that for trisomy 21. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.